Assembly of peptide linker to amino acid dehydrogenase and immobilized with metal–organic framework. Issue 3 (1st November 2021) - Wang, Shiyan; Duan, Lingxuan; Jiang, Liang; Liu, Kailong; Wang, Shizhen
Abstract: BACKGROUND: The metal–organic framework (MOF) ZIF‐8 has the advantages of a large specific surface area and high stability. A new strategy for the assembly of amino acid dehydrogenase with peptide linker and for improving enzyme immobilization is proposed. RESULTS: Peptide linker enhanced enzyme activity after immobilization by 138.7%, and maintained 81.2% of its initial activity after seven recycles. The stability of PheDH_1D02/ZIF‐8 was greatly enhanced at 70–80 °C and pH 10–11. The catalytic efficiency of PheDH_1D02/ZIF‐8 was also enhanced compared with PheDH_1C1D/ZIF‐8 and two free enzymes. CONCLUSIONS: Metal ions coordinated with the peptide linker and reoriented immobilization of enzyme onto the MOF with high enzyme loading capacity were achieved. The mesoporous structure of PheDH_1D02/ZIF‐8 facilitates substrate diffusion. Combining the assembly of peptide linker and MOF immobilization is a simple, economical and efficient method for improving dehydrogenase stability. © 2021 Society of Chemical Industry (SCI).